We Move or Are We Moved? Unpicking the Origins of Voluntary Movements to Better Understand Semivoluntary Movements - Virameteekul, Sasivimol; Bhidayasiri, Roongroj (Frontiers in Neurology, 2022)
The capacity for voluntary control is seen as essential to human movements; the sense that one intended to move (willing) and those actions were self-generated (self-agency) gives the sense of voluntariness and of being in control. While the mechanisms underlying voluntary movement have long been unclear, recent neuroscientific tools have identified networks of different brain areas, namely, the prefrontal cortex, supplementary motor area, and parietal cortex, that underlie voluntary action. Dysfunction in these brain areas can result in different forms of semivoluntary movement as the borderland of voluntary and involuntary movement where a person may experience a disordered sense of will or agency, and thus the movement is experienced as unexpected and involuntary, for an otherwise voluntary-appearing movement. Tics, functional movement disorders, stereotypies, perseveration, compulsions, utilization behaviors, and motor mannerism have been described elsewhere in the context of psychoses, and are often mistaken for each other. Yet, they reflect an impairment of prefrontal cortices and related circuits rather than simple motor systems, which results in the absence of subjective recognition of the movements, in contrast to other neurological movement disorders where principal abnormalities are located within the basal ganglia and its connections. Therefore, their recognition is clinically important since they are usually associated with neurodevelopmental and neurodegenerative disorders. In this review, we first defined a conceptual framework, from both a neuroanatomical and a neurophysiological point of view, for the generation of voluntary movement. We then examined the evidence linking dysfunctions in different motor pathways to each type of movement disorder. We looked at common semivoluntary movement disorders providing an overview, where possible, of their phenomenology and brain network abnormalities for each condition. We also emphasized important clinical feature similarities and differences to increase recognition of each condition in practice.